Effect of music therapy on sleep quality in elderly: A systematic review and meta-analysis - Cheng Li; Archana Prabu Kumar; Dapkupar Wankhar; Maheshkumar Kuppusamy; Karuppasamy Govindasamy (PLoS ONE, 2025)
Background Sleep disturbances are common among older adults, affecting up to 50% of this population and significantly impacting quality of life and health outcomes. Music therapy has been proposed as a non-pharmacological intervention to improve sleep quality in this population, but evidence regarding its effectiveness remains inconsistent across individual studies. Therefore, this systematic review and meta-analysis aims to synthesize available evidence on the effectiveness of music therapy interventions for improving sleep quality in elderly adults.. Methods We conducted a systematic review and meta-analysis following PRISMA guidelines. Major databases were searched for studies evaluating music interventions for sleep quality in adults aged 50 + years. Randomized controlled trials (RCTs) and non-randomized controlled trials (non-RCTs) were included. Risk of bias was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool for RCTs and the Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) tool for non-RCTs. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated using both common effect and random effects models. The certainty of evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Results The initial search retrieved 473 articles from electronic databases. After removing duplicates and screening, 10 studies (6 RCTs, 4 non-RCTs) published between 2010 and 2023 with 602 participants met inclusion criteria and were included in the meta-analysis. The random effects model showed significant improvement in sleep quality with music therapy (SMD: −0.79; 95% CI, −1.25 to −0.33; P < .001). Substantial heterogeneity was observed (I² = 79%; Q = 42.54; P < .001). Subgroup analysis revealed significant benefits in RCTs (SMD: −0.59; 95% CI, −1.11 to −0.07) but not in non-RCTs (SMD: −1.08; 95% CI, −2.36 to 0.19). Sensitivity analyses confirmed the robustness of findings, and no publication bias was detected. GRADE assessment indicated very low certainty of evidence for both RCTs and non-RCTs due to risk of bias concerns and substantial heterogeneity. Conclusions Music therapy demonstrates significant improvement in sleep quality among older adults; however, the very low certainty of evidence based on GRADE assessment suggests caution in clinical recommendations. Future research should address methodological limitations, particularly regarding bias in outcome measurement and intervention implementation, to provide more definitive evidence for clinical practice guidelines.